Management of atopic dermatitis via oral and topical administration of herbs in murine model: a systematic review - Mohd Kasim, Vivi Nur Khalieda; Noble, Siti Mahirah; Liew, Kong Yen; Tan, Ji Wei; Israf, Daud Ahmad; Tham, Chau Ling (Frontiers Research Foundation, 2022)
Over the past few decades, complementary and alternative medicine (CAM) using herbs, or their active constituents have garnered substantial attention in the management of a chronic and relapsing inflammatory skin disorder called atopic dermatitis (AD), particularly in attenuating disease recurrence and maintaining long-term remission. In Eastern Asian countries including China, Korea and Taiwan, herbal medicine available in both topical and oral preparation plays a significant role in treating skin diseases like AD as they possibly confer high anti-inflammatory properties and immunomodulatory functions. Conventional murine models of AD have been employed in drug discovery to provide scientific evidence for conclusive and specific pharmacological effects elicited by the use of traditional herbs and their active constituents. Coupled with the goal to develop safe and effective novel therapeutic agents for AD, this systematic review consists of a summary of 103 articles on both orally and topically administered herbs and their active constituents in the murine model, whereby articles were screened and selected via a specialized framework known as PICO (Population, Intervention, Comparator and Outcome). The objectives of this review paper were to identify the efficacy of oral and topical administered herbs along with their active constituents in alleviating AD and the underlying mechanism of actions, as well as the animal models and choice of inducer agents used in these studies. The main outcome on the efficacy of the majority of the herbs and their active constituents illustrated suppression of Th2 response as well as improvements in the severity of AD lesions, suppression of Immunoglobulin E (IgE) concentration and mast cell infiltration. The majority of these studies used BALB/c mice followed by NC/Nga mice (commonly used gender–male; commonly used age group – 6–8 weeks). The most used agent in inducing AD was 2, 4-Dinitrochlorobenzene (DNCB), and the average induction period for both oral and topical administered herbs and their active constituents in AD experiments lasted between 3 and 4 weeks. In light of these findings, this review paper could potentially assist researchers in exploring the potential candidate herbs and their active constituents using murine model for the amelioration of AD.